Diseño de un sistema de control interno para la “Cooperativa de ahorro y crédito Policía Nacional Ltda. Sucursal Loja”, de la ciudad de Loja. - Viteri Viteri, Danny Damián (2019)
The thesis work called DESIGN OF AN INTERNAL CONTROL SYSTEM FOR THE "COOPERATIVE OF SAVINGS AND CREDIT POLICÍA NACIONAL LTDA. SUCURSAL LOJA ", OF THE CITY OF LOJA., Is aimed at promoting an adequate management of resources and determining the proper administrative-financial functioning of the cooperative in order to seek the effectiveness, efficiency and economy of business management. In compliance with the proposal and one of the specific objectives, Internal Control standards are suggested to improve the order and optimization of human, material and financial resources; that helps managers achieve reasonable achievement of cooperative goals and objectives; the integration and assimilation of the personnel for the purposes of the organization and therefore to improve it avoiding fraud and internal corruption. Therefore, procedures with administrative and financial focus are considered, which allow to safeguard the resources, especially in the location and recovery of credit portfolio; as part of the internal control procedures, a manual of functions oriented to the workers is established to avoid duplication of functions, contributing to the efficiency and effectiveness of the cooperative objectives; Likewise, a manual of procedures is proposed which clearly details the purpose, scope and procedure for each primary activity carried out by each of the different departments of the cooperative, which workers must comply with in order to favor with the veracity and accuracy of the information. financial and administrative. Finally, flowcharts are developed for administrative and financial activities, thus facilitating their understanding by using technical flow diagrams that detail in a logical and sequential manner the process to be followed, in order to promote the quality of the activities that it executes by accessing implement new aspects of control that allow reaching the cooperative objectives of the same.